NUEVOS FOSILES DEL CRETACICO SUPERIOR (MAESTRICHTIANO) DEL DEPARTAMENTO MALARGÜE, PROVINCIA DE MENDOZA, ARGENTINA (Ameghiniana, 2013)
A Maestrichtian faunule is described, which was collected at Malargüe, Province of Mendoza. The species are related with those known from Huantraicó, of the same age.